THE INFLUENCE OF PEER ENVIRONMENT ON LEARNING MOTIVATION OF CLASS XI STUDENTS OF AL-AZHAR SENIOR HIGH SCHOOL, MEDAN - Hany Ataqiya Afan; Mohammad Fadel Hakeem; Ijlal Habibie; M. Ihza Al Amin (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
This study aims to determine the influence of the friendship environment on the learning motivation of grade XI students of Al Azhar Superior High School Medan. The research uses a quantitative approach with an associative descriptive method. The population in the study was determined through random sampling techniques. Data collection was carried out using a Likert scale questionnaire which included two main variables, namely the friendship environment and learning motivation. The results of the study show that the friendship environment has a positive influence on students' learning motivation. Most respondents stated that their friends supported learning activities (68.9%) and did not influence them not to study (53.3% disagreed). In addition, 82.2% of students admitted to studying earnestly and 100% trying to understand the lessons given. These findings show that a positive friendship environment contributes to increased student learning motivation in excellent schools.